Larvicidal potential of extracts and isolated compounds from Piper cubeba fruits against Aedes aegypti (Diptera: Culicidae) larvae - Gomes, Ana Carolina [UNESP]; Borges, Alexandre; Zoca, Daniela Garcia; Silva, Marcio Luís Andrade e; Machado, Aline Rafaela da Silva Rodrigues; Machado, Alex Martins; Santos, Mario F. C.; de Laurentiz, Rosangela da Silva [UNESP] (Taylor & Francis, 2022)
Aedes aegypti is the primary vector of virus transmission that causes dengue, yellow fever, chikungunya and zika. The primary prevention method has been vector control and synthetic insecticides that can cause environmental side effects. Thus, the work aimed to evaluate the larvicidal potential of extracts and isolated compounds from Piper cubeba against A. aegypti larvae. The larvicidal activity method was executed according to the World Health Organization protocol. The larvae were analyzed by scanning electron microscopy (SEM). Through molecular docking, the action mechanism was investigated. The hydroalcoholic and hexane extracts showed similar larvicidal activity with LC50 of 191.1 μg/mL and 185.84 μg/mL, respectively. Between isolated compounds, hinokinin presented LC50= 97.74 μg/mL. The SEM analysis showed structural damage to the larva’s tegument caused by extracts and isolated compounds. Therefore, the results demonstrate the larvicidal action of hinokinin and extracts, which can lead to the development of new natural larvicides.
Keywords: hinokinin; larvicidal activity; lignans; UDP-N-acetylglucosamine pyrophosphorylase